ANALISIS UNSUR INSTRINSIK DAN NILAI MORAL DALAM CERPEN “ROBOHNYA SURAU KAMI” KARYA ALI AKBAR NAVIS - Sri Rahayuningsih (IKIP Siliwangi, 2021)
This research was conducted out on the backround of researchers’ curiosity about instrinsic elements and moral values in one of the short stories by Ali Akbar Navis entitled “Robohnya Surau Kami”. This research was conducted by analyzing using qualitative descriptive methods. The purpose of study is to describe the cohesiveness between intrinsic elements and moral values contained inthe short story “Robohnya Surau Kami” by Ali Akbar Navis. Analyzing this short story is done by collecting data as follows : reading the short story “Robohnya Surau Kami”, analyzing the instrinsic elements and moral values contained in it. After conducting research by analyzing it, it turns out that Ali Akbar Navis’s efforts in combining instrinsic elemennts consisting of : theme, plot, setting, characterization, languange style, point of view and mandate are done well so that the uniqueness and systematicityof his story are well conveyed. In addition, the moral values contained in this short stiry are conveyed clearly to the reader which contains the views that must be applied in life.